Registration of 'CP 08‐1968' Sugarcane. Issue 2 (11th April 2019) - Davidson, R. Wayne; Scott, Andy W.; Hernandez, Eduardo; Gordon, Vanessa S.; McCord, Per; Sandhu, Hardev S.; Zhao, Duli; Comstock, Jack C.; Sood, Sushma; Singh, Maninder P.; Islam, Md. S.; Baltazar, Miguel; et al.
Abstract : 'CP 08‐1968' (Reg. No. CV‐185; PI 687332) sugarcane (a complex hybrid of Saccharum spp.) cultivar was developed through cooperative research conducted by the USDA‐ARS, the University of Florida, and the Florida Sugarcane League, Inc. At the 5 June 2017 Florida Sugarcane Variety Committee Meeting, CP 08‐1968 was released to growers for all soils in Texas; seedcane became available in September 2018. At the 30 Oct. 2017 Florida Sugarcane Variety Committee Meeting, CP 08‐1968 was approved as a co‐release to growers with sand soils in Florida and all soils in Texas. CP 08‐1968 was selected from a biparental cross of CP 01‐1178 × CP 00‐1301 made at Canal Point, FL, in November 2006. The female parent, CP 01‐1178, and the male parent, CP 00‐1301, are not commercial cultivars. Cane yield of CP 08‐1968 on sand soils in Florida, averaged across nine harvests through three crop cycles (plant‐cane, first‐ratoon, and second‐ratoon), was 15.0 and 10.1% higher ( P < 0.1) than that of CL 88‐4730, a commercial check for sand soils, and CP 89‐2143, a high commercial recoverable sucrose (CRS) commercial check for muck and sand soils. Although CP 08‐1968 had 2.8 and 6.0% lower CRS than CL 88‐4730 and CP 89‐2143, respectively (Glaz et al., 2000), high cane yield resulted in 11.3 and 2.1% higher ( P < 0.1) sucrose yield than CL 88‐4730 and CP 89‐2143, respectively. CP 08‐1968 was released because of its high cane and sucrose yields on sand soils, as well as its acceptable levels of resistance to brown rust, smut, Sugarcane mosaic virus strain E (mosaic), Sugarcane yellow leaf virus (Comstock et al., 1999), and ratoon stunt. CP 08‐1968 is susceptible to orange rust and has moderate to good freeze tolerance. CP 08‐1968 tested negative for the Bru 1 quantitative trait locus, which is an indicator of brown rust resistance.